2009
DOI: 10.1007/s00011-009-0044-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CD203c membrane up-regulation in human basophils by high dilutions of histamine: a controlled replication study

Abstract: Objective Previous research suggests that human basophil activation may be inhibited by histamine even at extremely low doses (high dilutions). However, uncertainties about the nature of the phenomenon and its reproducibility mean that further, rigorously controlled studies are necessary. Methods Serial 1:100 (v:v) histamine dilutions (centesimal dilutions, C) and water controls were tested on human basophil responsiveness to anti-IgE antibodies, using flow cytometry. Each dilution step was followed by vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 48 publications
(62 reference statements)
1
38
0
1
Order By: Relevance
“…The mechanism resulting in impaired basophil activation in vitro remains unknown. Suppression of CD203c by endogenous histamine, (6) or impaired activation due to a refractory state, are possible explanations. (E3) Caution must be exercised with regard to generalization of the identified associations given the small sample size and preliminary nature of this report; additional discretion must be exercised with regard to those data which were derived from a sub-population of our cohort.…”
Section: To the Editormentioning
confidence: 99%
“…The mechanism resulting in impaired basophil activation in vitro remains unknown. Suppression of CD203c by endogenous histamine, (6) or impaired activation due to a refractory state, are possible explanations. (E3) Caution must be exercised with regard to generalization of the identified associations given the small sample size and preliminary nature of this report; additional discretion must be exercised with regard to those data which were derived from a sub-population of our cohort.…”
Section: To the Editormentioning
confidence: 99%
“…Thus, our results, obtained in fully randomized, controlled and blind conditions, confirm and reinforce the observations -emerging from several research fields -that biologically active compounds may indeed have high-dilution effects which mimics those of lower dilutions (higher doses): in homeopathy there does not exist linearity or proportionality between molecular concentration of active principles and biological effect. 39,41,[67][68][69][70][71] So far there is no uniting theoretical explanation for these observations, but recent hypotheses seem to point to organisation of the solvent water on a mesoscopic scale: the nano-heterogenous structure of water can be determined by interactive phenomena such as coherence, epitaxy, temperature-pressure processes during strong agitation, and formation of colloidal nanobubbles containing gaseous inclusions of oxygen, nitrogen, carbon Assays of homeopathic remedies in rodents P Bellavite et al dioxide, silica, and possibly the remedy source material. [72][73][74][75][76][77][78][79] We have also previously suggested a analogy between this type of non-linearity and a hypothetical fractal-type organisation of water nanoheterogeneities, [80][81][82] due to the iterative process of dilution/succussion.…”
Section: Effects In Animal Modelsmentioning
confidence: 99%
“…NPP3 expression is associated with carcinogenesis and metastasis of cancer cells and has been proposed as a tumor marker [1,10,17]. Additionally, it has been reported that this enzyme is expressed by basophils and mast cells where it might have a function in the activation process of these cells [4,18].…”
Section: Introductionmentioning
confidence: 99%